2018
DOI: 10.1159/000492874
|View full text |Cite
|
Sign up to set email alerts
|

Imperatorin Targets MCL-1 to Sensitize CD133+ Lung Cancer Cells to γδ-T Cell-Mediated Cytotoxicity

Abstract: Background/Aims: CD133+ cancer cells display low sensitivity to anti-cancer treatment; thus, combination treatment with adjuvant drugs is required to improve the efficiency of cancer therapy. The aim of this study was to explore the effect of imperatorin, a linear furanocoumarin compound, on γδ T cell-mediated cytotoxicity against CD133+ lung cancer cells. Methods: CD133+ and CD133- subgroups from A549 and PC9 lung cancer cells were sorted by using flow cytometry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Imperatorin, known as ammidin, marmelide, and marmelosin, is a naturally occurring active furocoumarin and phytochemical that is mainly found in citrus fruits (such as Citrus grandis and Citrus maxima ) and some species of the genus Angelica that are used as medicine (such as Angelica biserrate , Angelica dahurica , Angelica archangelica , Angelica pubescens and Angelica albicans ). It is known to exert many pharmacological properties, including anti-inflammatory effects on inflammation-associated lung, liver, osteoarthritis, ulcerative colitis, and neuro diseases [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] as well as anticancer [ 21 , 22 , 23 , 24 ] and antiviral activities [ 25 , 26 , 27 ]. A recent study has shown that imperatorin IMP can ameliorate PS-induced learning and memory deficits through the BDNF/TrkB and ERK/CaMKIIα/CREB signaling pathways and the hypothalamic–pituitary–adrenal axis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imperatorin, known as ammidin, marmelide, and marmelosin, is a naturally occurring active furocoumarin and phytochemical that is mainly found in citrus fruits (such as Citrus grandis and Citrus maxima ) and some species of the genus Angelica that are used as medicine (such as Angelica biserrate , Angelica dahurica , Angelica archangelica , Angelica pubescens and Angelica albicans ). It is known to exert many pharmacological properties, including anti-inflammatory effects on inflammation-associated lung, liver, osteoarthritis, ulcerative colitis, and neuro diseases [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] as well as anticancer [ 21 , 22 , 23 , 24 ] and antiviral activities [ 25 , 26 , 27 ]. A recent study has shown that imperatorin IMP can ameliorate PS-induced learning and memory deficits through the BDNF/TrkB and ERK/CaMKIIα/CREB signaling pathways and the hypothalamic–pituitary–adrenal axis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, molecular docking and dynamics simulations validated the hypothesis that YFSJF inhibits PIK3R1, PIK3CA, and AKT1 to suppress the PI3K/ AKT pathway and fght NSCLC. After further literature review, it was found that the antitumor role of hub chemicals has been reported by many researchers, especially for lung cancer [54][55][56][57][58][59]. For instance, ginsenoside compound K, the major intestinal bacterial metabolite of ginsenoside Rb1, can induce apoptosis and autophagy in NSCLC cells by regulating the AMPK/mTOR pathway [54].…”
Section: Discussionmentioning
confidence: 99%
“…After further literature review, it was found that the antitumor role of hub chemicals has been reported by many researchers, especially for lung cancer [54][55][56][57][58][59]. For instance, ginsenoside compound K, the major intestinal bacterial metabolite of ginsenoside Rb1, can induce apoptosis and autophagy in NSCLC cells by regulating the AMPK/mTOR pathway [54]. Naringenin can induce Bax-mediated mitochondrial apoptosis in human lung adenocarcinoma A549 cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…Imperatorin was recognized to suppress cancer by halting cell cycle progression [ 145 ]. Moreover, imperatorin can augment the cytotoxicity of gamma-delta T cells against CD133-positive cancer via targeting myeloid cell leukemia 1 ( MCL1 ), an endogenous apoptosis inhibitor [ 146 ]. It was further shown that imperatorin inhibits TGF-β-mediated ERK activation, thus hindering metastasis [ 147 ].…”
Section: Natural Polyphenolic Compoundsmentioning
confidence: 99%